Pemetaan Bibliometrik dan Tinjauan Literatur atas Penelitian Good Corporate Governance: Temuan dari Analisis Vosviewer - Latifatul Hasanah; Sri Andriani (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to systematically map the development of literature on Good Corporate Governance (GCG) using a mixed-method approach that integrates bibliometric analysis with VOSviewer and a systematic literature review. The research focuses on publications from the last five years (2020–2024), with data collected using the Publish or Perish software and the keyword “Corporate Governance.” The initial search identified 772 relevant scientific articles that met the inclusion criteria. Through network visualization analysis using VOSviewer, the study reveals that GCG research can be categorized into four thematic clusters, each representing distinct areas of focus. These clusters highlight key topics such as corporate performance, board structure, stakeholder relations, and sustainability practices, reflecting the diverse and evolving nature of GCG research. The findings provide valuable insights into the intellectual structure and research trends within the field, offering a foundation for future scholarly exploration and practical application.